Pengaruh Kualitas Layanan, Kecepatan Transaksi, Dan Keamanan Data Terhadap Loyalitas Nasabah BRI-Mobile (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2021-2023) - Naba, Bachrul; Widarko, Agus; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Digital transformation has significantly brought changes to the way work is conducted across various economic sectors, including the financial industry. This study aims to analyze the loyalty of BRImo customers among students of Universitas Islam Malang (UNISMA) from the 2021-2023 batch. The research uses a quantitative method with students from the 2021-2023 batch of UNISMA as the selected population. The respondents involved in this study number 100 individuals, chosen using purposive sampling as the sampling technique. The data used in this research consists of both secondary and primary data, which are then processed using SPSS version 25. The results of the study conclude that service quality (X1), transaction speed (X2), and data security (X3) simultaneously affect customer loyalty (Y). Furthermore, the variables of transaction speed (X2) and data security (X3) have a partial effect on customer loyalty (Y), while service quality (X1) does not have an effect on customer loyalty (Y). Keywords: Customer Loyalty, Service Quality, Transaction Speed, Data Security, Digital Transformation